FAKTOR FAKTOR YANG MEMENGARUHI RENDAHNYA PENGGUNAAN (AKDR) - Novitasari; Siti Fatimah (Institut Citra Internasional, 2026)
IUD is one of the family planning methods that is classified as a long-term contraceptive method. IUD is a device or object inserted into the uterus that is very effective and can be used by all women of productive age. The achievement of the IUD family planning program in the Kelapa Community Health Center Working Area is still low, especially the PUS using IUD has not experienced a significant increase. The purpose of this study is to determine the factors that influence the low use of IUD in the Kelapa Community Health Center Working Area, West Bangka Regency in 2025. This study used a case control design with a sample of active family planning acceptors in the Kelapa Community Health Center Working Area divided into 2 groups of cases and controls. The case group is 40 IUD family planning acceptors, while the control group is 40 non-IUD family planning acceptors based on medical record data from the Kelapa Community Health Center in 2024. Based on the results of the study, there is a significant relationship between parity (p-value 0.045), education (p-value 0.001), the role of health workers (p-value 0.024), history of contraceptive use (p-value 0.004) on the low use of IUDs in the Kelapa Health Center Working Area in 2025. The suggestion of this study is that health workers can provide counseling training to health cadres so that they can effectively promote the use of IUDs in Posyandu.